Music-based emotion regulation: a bibliometric systematic review (2000–2024) - Lu, Xixi; Song, Shijie (Frontiers in Psychology, 2025)
BackgroundMusic Emotion Regulation (MER) research has emerged as a significant field in mental health intervention, yet a comprehensive bibliometric analysis of its development and current status is lacking.PurposeThis research aims to systematically analyze the knowledge structure, research trends, and development patterns in MER research through bibliometric analysis.MethodsUsing data from the Web of Science Core Collection (2000–2024), we conducted a comprehensive bibliometric analysis using R for primary analyses. We examined publication trends, collaboration networks, research themes, and emerging directions through multiple bibliometric indicators including co-citation analysis, keyword co-occurrence, and research theme evolution.ResultsThe analysis revealed three distinct development phases of MER research: initial exploration (2000–2009), rapid growth (2010–2019), and maturation (2020–2024). Research in the field demonstrates a clear transition from theoretical foundations to practical applications, with increasing methodological sophistication and cross-disciplinary integration. International collaboration networks show a “tri-polar” pattern centered in East Asia, Europe, and North America, with distinctive regional research characteristics.ConclusionMER research has evolved into a mature, interdisciplinary field with robust theoretical foundations and practical applications. Future development trends point toward increased integration of artificial intelligence, personalized intervention strategies, and expanded international collaboration.